BENEFITS OF OAT MILK - Aminova Mohirakhon Mo'minjon qizi; Nazirova Rahnamokhon Mukhtorovna (TADQIQOTLAR, 2025)
Annotation:This article explores the growing popularity and diverse health, environmental, and practical benefits of oat milk as a leading plant-based alternative to traditional dairy. It examines its nutritional profile, focusing on its high fiber content (particularly beta-glucans), low saturated fat, and absence of lactose, which make it a favorable choice for individuals with dietary restrictions, including lactose intolerance and nut allergies. Furthermore, the article discusses the sustainability advantages of oat milk production compared to dairy and other plant-based milks, analyzing its lower water and land usage. The paper concludes by evaluating its culinary versatility and market acceptance, solidifying its position as a significant component of modern, health-conscious diets.